Land Use and Ecosystem Service Value Spatiotemporal Dynamics, Topographic Gradient Effect and Their Driving Factors in Typical Alpine Ecosystems of the East Qinghai‐Tibet Plateau: Implications for Conservation and Development - Bin Feng; Jianwei Zhou; Lu Hu; Zherong Liu; Yi Yang; Shuai Yang; Jianying Ni; Wenke Bai; Shanshan Zhao (Ecology and Evolution)
ABSTRACT Shiqu County, China, represents a vital component of alpine ecosystems on the eastern Qinghai‐Tibet Plateau, playing a pivotal role in regional ecological functions. However, amid the backdrop of climate change and rapid land‐use transformation, its delicate alpine ecosystems remain persistently threatened by human activities, including several nature reserves and a Ramsar site within it. This paper analyzes the temporal and spatial evolution and differentiation of Ecosystem Service Value (ESV) in Shiqu County (1980–2020), focusing on its driving factors. The research findings reveal that: (1) From 1980 to 2020, Shiqu County experienced a general trend of diminishing unused land, grassland, and cultivated land, alongside an expansion of forested land, water areas, and construction land. (2) Throughout the study duration, the ESV of Shiqu County exhibited a growth trajectory, escalating from 26.180 billion CNY in 1980 to 26.848 billion CNY in 2020, representing a net increase of 2.55%. Grasslands played the most substantial role in contributing to Shiqu's ESV. (3) From 1980 to 2020, all ecosystem service functions exhibited ESV growth, with hydrological regulation and water supply notably increasing by 9.07% and 8.81%, respectively. (4) Land‐use distribution demonstrates significant vertical zonation along gradients of altitude, slope, aspect, and terrain ruggedness, resulting in pronounced vertical variations in ESV, per unit area ESV, and ESV across various ecosystem service functions. (5) The spatial differentiation of ESV in Shiqu County is influenced by both natural and economic factors, with natural factors exerting a more substantial influence on spatial disparities than economic factors. The research provides insights to guide policymakers in prioritizing conservation efforts in fragile alpine ecosystems and optimizing land‐use strategies to achieve sustainable development goals, offering a transferable framework for similar regions globally.